Determination of oxygen in acid-treated high-purity niobium by X-ray photoelectron spectroscopy. Issue 2 (3rd March 2016) - Wang, Kuan; Li, Bo; Sun, Baolian; Wang, Pengwei; Zhou, Kai; Zheng, Wei; Liang, Qinghua
ABSTRACT: High-purity niobium was immersed in nitric acid and hydrofluoric acid for two minutes and the resulting product was characterized. Scanning electron microscopy was employed to characterize the morphology of the acid treated product. Inert gas fusion was used for determination of oxygen in the high-purity niobium. X-ray photoelectron spectroscopy was employed to characterize the surface ratio of oxygen to niobium. The oxygen concentration was 30 ppm in the acid-treated material and 70 ppm in the untreated material. X-ray photoelectron spectroscopy was employed to characterize the reduction of oxygen at the surface. The ratio of oxygen to niobium decreased from 9.75 to 2.60 without treatment compared to acid treatment for two minutes. The concentrations of adsorbed water and niobium oxide decreased following etching. The acid-treated high-purity niobium was characterized by argon ion bombardment; adsorbed water molecules and niobium oxides were not present but non-lattice oxygen was observed.